The GRDP per capita, human development index, open unemployment rate, regional expenditure, and poverty in East Java Province - Falah, Meilita Arini; Rahmawati, Farida (Jurnal Ekonomi & Studi Pembangunan, 2024)
Poverty is one of the goals of Indonesia's development program, as stated in the first point of the Sustainable Development Goals (SDGs). East Java Province has one of the largest poor populations in Indonesia, making poverty reduction a major component of improving people's welfare. This study aims to ascertain the effect of GRDP per capita, Human Development Index (HDI), Open Unemployment Rate, and regional expenditure in East Java Province from 2012 to 2022. The findings are expected to be a reference or policy-making decision in poverty alleviation efforts. This study makes use of panel data from East Java Province's 38 districts and cities from 2012 to 2022. Quantitative analysis method is utilized with an error correction model (ECM) regression analysis technique. The results showed that GRDP per capita, HDI, unemployment, and regional expenditure simultaneously affect poverty in East Java Province. Partially, GRDP per capita and HDI have a negative effect on poverty both in the long and short-term. In the long term, unemployment has a positive effect on poverty, but shows no effect in the short term . Meanwhile, regional expenditure has no effect on poverty, either in the long or short term in East Java Province. Reducing poverty can be achieved by increasing economic output to increase per capita income, improving the quality of human resources through investment in education and health, providing broad employment opportunities to reduce unemployment, and increasing the allocation of regional expenditure and allocation of regional expenditure with the right target.